Organic semiconductor rubrene thin films deposited by pulsed laser evaporation of solidified solutions - Majewska N; Gazda M; Jendrzejewski R; Majumdar S; Sawczak M; Sliwinski G (My University, 2022)
Organic semiconductor rubrene (C42H28) belongs to most preferred spintronic materials because of the high charge carrier mobility up to 40 cm(2)(V.s)(-1). However, the fabrication of a defect-free, polycrystalline rubrene for spintronic applications represents a difficult task. We report preparation and properties of rubrene thin films deposited by pulsed laser evaporation of solidified solutions. Samples of rubrene dissolved in aromatic solvents toluene, xylene, dichloromethane and 1,1-dichloroethane (0.23-1% wt) were cooled to temperatures in the range of 16.5-163 K and served as targets. The target ablation was provided by a pulsed 1064 nm or 266 nm laser. For films of thickness up to 100 nm deposited on Si, glass and ITO glass substrates, the Raman and AFM data show presence of the mixed crystalline and amorphous rubrene phases. Agglomerates of rubrene crystals are revealed by SEM observation too, and presence of oxide/peroxide (C42H28O2) in the films is concluded from matrix-assisted laser desorption/ionization time-offlight spectroscopic analysis.
Third International Conference on Applications of Optics and Photonics